The effect of motor coordination exercises on developing certain biomechanical abilities specific to junior football players - باييز, رزكار محمد; محمد, ا.د ئاوات لحمد فقي (Sulaimani Journal for Humanities, 2025)
The research aimed to develop a training program for improving certain biomotor skills in junior football players, to identify differences between pre-tests and post-tests in developing these skills, and to determine the differences in post-test results. The researcher employed an experimental method using two equivalent groups, as this approach was suitable for the nature of the research problem. The research population consisted of players from the Peshmerga Sports Club, and a purposive sample of 30 players was selected. The exercises were determined using scientific sources and references, and a suitable test for measuring scoring was identified. A pilot study was conducted to identify obstacles and ensure the homogeneity of the research sample. Following this, a pre-test was administered, and the proposed exercise program was implemented for eight weeks, with three exercises per week, totaling 24 learning units. The researcher then conducted a post-test and used appropriate statistical methods. The researchers concluded that the motor coordination exercises had a positive impact on physical abilities, and that the experimental group, which used the motor coordination exercises program, outperformed both the experimental and control groups in physical abilities.
Keywords: Motor coordination; biomechanics; fluidity; targeting